2008
DOI: 10.1590/s1414-98932008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais da depressão e do suicídio elaboradas por estudantes de psicologia

Abstract: O presente estudo aborda a depressão e o suicídio, dois sérios problemas de saúde pública, sob um enfoque psicossociológico, com o objetivo de apreender as representações sociais acerca desses dois fenômenos bem como de investigar a sua ocorrência no meio acadêmico. Participaram da pesquisa 233 estudantes de ambos os sexos, matriculados em todos os períodos do curso de Psicologia de uma universidade pública. Os instrumentos utilizados foram o inventário de depressão de Beck (BDI), a escala de ideação suicida d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
5
0
14
Order By: Relevance
“…Gonçalves et al (2014), in an investigation with students from the Polytechnic Institute of Viseu (Portugal), verified that about 8% of the students had suicidal ideation in the month prior to their participation in the study, which is an approximate value to the one obtained here. Similarly, in investigations involving students from Latin American cultures, prevalences of 7.9% (Finger & Argimon, 2013), 11% (Vieira & Coutinho, 2008), 13.4% and 12.3% (Alexandrino-Silva et al, 2009) were found. Cavestro and Rocha (2006) also estimated that 9.6% of their sample was at risk of committing suicide, with the prevalence of suicidal ideation varying between 7.5% for medical students and 25.6% for occupational therapy students.…”
Section: Discussionmentioning
confidence: 83%
“…Gonçalves et al (2014), in an investigation with students from the Polytechnic Institute of Viseu (Portugal), verified that about 8% of the students had suicidal ideation in the month prior to their participation in the study, which is an approximate value to the one obtained here. Similarly, in investigations involving students from Latin American cultures, prevalences of 7.9% (Finger & Argimon, 2013), 11% (Vieira & Coutinho, 2008), 13.4% and 12.3% (Alexandrino-Silva et al, 2009) were found. Cavestro and Rocha (2006) also estimated that 9.6% of their sample was at risk of committing suicide, with the prevalence of suicidal ideation varying between 7.5% for medical students and 25.6% for occupational therapy students.…”
Section: Discussionmentioning
confidence: 83%
“…38 SUICÍDIO X DEPRESSÃO X DESESPERANÇA Apontando para uma relação estreita entre a depressão e o suicídio, a conduta suicida pode ser considerada como um dos sintomas do transtorno depressivo. 39…”
Section: Causas Da Depressãounclassified
“…A utilização da TALP permite um tipo de investigação aberta, que se estrutura através da evocação de respostas dadas a partir de um ou mais estímulos indutores. Esses estímulos indutores devem ser previamente definidos em função do objeto a ser pesquisado ou do objeto da representação, levando-se também em consideração as características da amostra ou os sujeitos da pesquisa (Vieira & Coutinho, 2008). Assumindo a Teoria das Representações Sociais de Moscovici (1961) como quadro analítico e recordando a perspetiva de Durkheim (1964) de que os factos sociais resultam da construção de representações simbólicas partilhadas pelos membros de sistemas sociais, procurámos através desta metodologia identificar quais as conceituações formais que expressam as representações sociais do envelhecimento ativo.…”
Section: Métodounclassified